Enhanced Image Encryption Using Two Chaotic Maps - Fatimah Abdulnabi Salman; Khitam Abdulnabi Salman (LPPM ITB, 2020)
Information security is an important aspect in various communication areas, multimedia frameworks, medical imaging and militant communications. However, most of them encounter issues such as insufficient robustness or security. Recently, the approach of achieving information security by using chaotic techniques has gained popularity, since they provide ergodic and random generated keys. This paper introduces a combination of two chaotic maps (3D logistic map and Arnold's cat map) that meet the general security requirements of image transmission. First the image is encrypted using Arnold's cat map, which shuffles the image pixels. 3D logistic map is applied to the encrypted image for transformation and permutation purposes. Then the XOR operation for the encrypted image and a chaotic sequence key are used to provide more security after the pixel values have been changed. The performance of the proposed security method was evaluated using MATLAB by analyzing the correlation between adjacent pixels, histogram analysis, and entropy information. The simulation results showed that the proposed method is robust and resilient. It can achieve an average of 7.99 for entropy information, 99.6% for NPCR, and 33.77 % for UCAI.